Improvement of sweet potato yield using mixtures of ground fish bone and plant residues - A C Novianantya; N K Fardany; Y Nuraini (Brawijaya University, 2017)
The Indonesian government begins to promote food diversification program. The government expects the Indonesian people can consume food crops other than rice, such as wheat, potatoes and sweet potatoes. While, the level of production of sweet potato production decreased in the period of 2012-2015 with total production of only 2,218,992 t/ha. In an effort to increase the production of sweet potato, improvements are needed through application of organic fertilizers like composts. The purpose of this study was to explore the effect of composted manure with ground fish bone, legume residues, and Tithonia on soil chemical properties and sweet potato production includes tuber weight and levels of starch sweet potato crops.The results showedthat application of 5 t compost/ha and 35 kg Trichoderma biofertilizer/ha increased pH, water content, organic carbon, total N, available P, total Kl, CEC,exchangeable Ca, plant height, tuber weight and levels of sweet potato starc